DIAGNOSTIC VALUES OF ULTRASOUND MEASUREMENTS OF THE MEDIAN NERVE IN PATIENTS WITH CARPAL TUNNEL SYNDROME - Grujoska-Veta, Dushanka; Toleska, Roze Dzoleva; Velkovski, Vilijam; Osmani, Bashkim; Gucev, Filip; Bogdanska, Jasna (Journal of Morphological Sciences; Vol 3 No 3 (2020): JMS, 2020)
Carpal tunnel syndrome (CTS) is the most common peripheral neuropathy of the upper extremity, caused by chronic compression of the median nerve in the area of the carpal tunnel with prevalence in females. The diagnosis is based on characteristic symptoms and signs, clinical findings, electroneuromyographic examination (ENMG) and diagnostic imaging.The aim of our study is to determine the role of ultrasound examination (US) of the median nerve in patients with CTS .A prospective clinical study included 116 patients with clinical diagnosis of CTS and positive findings of ENMG examination who were admitted for surgical procedure of open carpal tunnel release. US examination of carpal tunnel and the median nerve were done in all patients on transverse and longitudinal axis of wrists. Measurements of the cross-sectional area (CSA) of the median nerve at inlet level revealed various grades of severity: mild, moderate and severe with CSA values of 10,9 -12,1 mm 2 ; 12,2 -15,3 mm 2 ;15,9-20,3mm 2 respectively. Correlation of severity grading of US measurements and ENMG findings was positive and statistically significant (p=0.000003, p=0.00006, and p<0.0001). Neuromuscular ultrasound examination provides valuable information on morphology of carpal tunnel content and possible etiology of CTS. Although dynamic imaging is used during US examination, measurements are done only on static scanning. It is used as additional tool in clinical practice of orthopedic surgeons and is very useful in early diagnosis, treatment planning and outcome follow-up. Kew words :carpal tunnel syndrome, ultrasound measurements, severity grading